2020
DOI: 10.1084/jem.20200388
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine depletion regulates Slug to promote EMT and metastasis in pancreatic cancer

Abstract: Tumor cells rely on glutamine to fulfill their metabolic demands and sustain proliferation. The elevated consumption of glutamine can lead to intratumoral nutrient depletion, causing metabolic stress that has the potential to impact tumor progression. Here, we show that nutrient stress caused by glutamine deprivation leads to the induction of epithelial–mesenchymal transition (EMT) in pancreatic ductal adenocarcinoma (PDAC) cells. Mechanistically, we demonstrate that glutamine deficiency regulates EMT through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 55 publications
5
81
0
Order By: Relevance
“…Due to the poor vascularization and hypoxic environment, PDAC tumors have been found to be commonly deprived of several nutrients, including glutamine (110). Pharmacologically, glutamine deprivation by glutamine analog DON leads to the induction of EMT through selectively up-regulating the EMT transcription factor Slug in both KPC mouse model and human PDAC cell lines, contributing to enhanced tumor migration and invasion capacities (111). Besides, under the hypoxic condition, Xiang et al found that GLS1 was implicated in hypoxia-induced cancer cell invasion and metastasis, where GLS1 knockdown significantly suppressed CRC cell migration and invasion in vitro, as well as tumor growth and metastatic colonization in vivo (64).…”
Section: Glutaminolysis and Cancer Metastasis: Emt Tumor Immunologymentioning
confidence: 99%
“…Due to the poor vascularization and hypoxic environment, PDAC tumors have been found to be commonly deprived of several nutrients, including glutamine (110). Pharmacologically, glutamine deprivation by glutamine analog DON leads to the induction of EMT through selectively up-regulating the EMT transcription factor Slug in both KPC mouse model and human PDAC cell lines, contributing to enhanced tumor migration and invasion capacities (111). Besides, under the hypoxic condition, Xiang et al found that GLS1 was implicated in hypoxia-induced cancer cell invasion and metastasis, where GLS1 knockdown significantly suppressed CRC cell migration and invasion in vitro, as well as tumor growth and metastatic colonization in vivo (64).…”
Section: Glutaminolysis and Cancer Metastasis: Emt Tumor Immunologymentioning
confidence: 99%
“…In this report, Recouvreux et al (2020) demonstrate a link between nutrient stress and EMT activation in PDAC cells, showing that glutamine deprivation plays a major part. Specifically, they report that glutamine limitation up-regulates the expression of EMT transcription factor Slug via MAPK signaling and ATF4 activation, a wellknown stress response pathway that gets activated in response to nutrient starvation.…”
mentioning
confidence: 53%
“…Not only could this decrease metastatic spread, but targeting Slug could also reduce the tumor's resistance to proapoptotic signals and cell death to engender improved responses to therapies. In closing, Recouvreux et al (2020)…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…These results suggest that the proproliferation and anti-apoptotic functions of KLK8 may not be dependent on activation of Notch signaling pathway. Notably, our GSEA analysis data showed that KLK8 overexpression might also lead to the activation of EMT (epithelial-mesenchymal transition), glycolysis and KRAS signaling pathway, which have been implicated in the pathogenesis and progression of pancreatic cancers [17,[43][44][45]. Whether these processes and the related signaling pathways contribute to the KLK8-induced pro-proliferation and anti-apoptotic effects in pancreatic cancers merits further investigation.…”
Section: Discussionmentioning
confidence: 84%